Factors of interruption of enteral nutrition in adult intensive care units: integrative review - Pinheiro, Denis dos Santos (2020)
Objective: to identify in the literature the main factors of interruption of enteral nutrition in adult intensive care units. Method: integrative literature review, made possible through data collection in the LILACS, Medline and Scopus databases, with chronological cut from 2010 to 2020. The search descriptors were used: “Nutrição Enteral” or “Enteral Nutrition”, “ Cuidados Críticos ”or“ Critical Care ”,“ Desnutrição ”or“ Malnutrition ”. Results: Of the 10 articles selected for reading and analysis, it was possible to identify that the main reasons for interruption of enteral diet were: 08 (80%) break for exams, procedures and surgeries, 06 (60%) gastrointestinal intolerance, 03 (30% ) extraction or difficulties with enteral access, 02 (20%) diarrhea and 02 (20%) due to clinical instability. Conclusion: The research allowed to identify in the literature the main factors causing interruption of enteral diet in intensive care units, pointing to some similarity between different countries and scenarios. Emerging in this way, the recommendation of new research on the topic, which proposes to evaluate the knowledge of health professionals about the theme of nutritional therapy, in order to guide the development of educational and training plans.